Cassava (Manihot esculenta Crantz) and Yam (Dioscorea spp.) Crops and Their Derived Foodstuffs: Safety, Security and Nutritional Value. Issue 16 (9th December 2016) - Ferraro, Vincenza; Piccirillo, Clara; Tomlins, Keith; Pintado, Manuela E.
Abstract : Cassava ( Manihot esculenta Crantz ) and yam ( Dioscorea spp. ) are tropical crops consumed by ca. 2 billion people and represent the main source of carbohydrate and energy for the approximately 700 million people living in the tropical and sub-tropical areas. They are a guarantee of food security for developing countries. The production of these crops and the transformation into food-derived commodities is increasing, it represents a profitable business and farmers generate substantial income from their market. However, there are some important concerns related to the food safety and food security. The high post-harvest losses, mainly for yam, the contamination by endogenous toxic compounds, mainly for cassava, and the contamination by external agents (such as micotoxins, pesticides, and heavy metal) represent a depletion of economic value and income. The loss in the raw crops or the impossibility to market the derived foodstuffs, due to incompliance with food regulations, can seriously limit all yam tubers and the cassava roots processors, from farmers to household, from small-medium to large enterprises. One of the greatest challenges to overcome those concerns is the transformation of traditional or indigenous processing methods into modern industrial operations, from the crop storage to the adequate package of each derived foodstuff.